BENEFITS OF ORGANIC FARMING IN PROMOTING SUSTAINABLE FOOD SECURITY - Rita Hayati; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Organic farming offers many benefits in supporting sustainable food security. Through environmentally friendly and synthetic chemical-free practices, organic farming maintains ecosystem health, improves soil fertility, and reduces negative impacts on the environment. In addition to its ecological benefits, the system also supports local economies by providing fairer returns to farmers and creating jobs, which in turn strengthens rural communities. Organic farming also plays an important role in education and awareness-raising about the importance of sustainable practices, thus preparing communities to face future challenges. Thus, organic farming contributes significantly to building sustainable food security that is ecologically, economically, and socially beneficial.